Masculinity Representation of Jacob Black Character in New Moon Movie - Rahma, Wijna Akhila (LANTERN (Journal on English Language, Culture and Literature), 2014)
The writer discussed about Jacob Black character in New Moon movie. There are three purposes of this study; to have knowledge about masculinity representation, to know more about Jacob Black character, and to be able to decide whether Jacob Black can be the representation of masculinity or not. The writer uses the masculinity theory by Frank Pittman. The result of the study shows that Jacob Black has the masculinity characteristics and, therefore, can be categorized as being the masculinity representative.